The Relationship Between Family Support and Quality of Life Among People Living with HIV/AIDS (PLHIV) At WPA Turen Foundation - Muhammad Rias Kurnia Sandi; Sih Ageng Lumadi; Ridwan Sofian (STIKep PPNI Jawa Barat, 2026)
Background: HIV/AIDS is a progressive chronic disease that adversely affects the physical, psychological, social, and spiritual dimensions of an individual's life. People living with HIV/AIDS (PLHIV) are particularly vulnerable to a decline in quality of life due to opportunistic infections, stigma, discrimination, and inadequate social support, including limited support from their families. Objective: This study aimed to analyze the relationship between family support and quality of life among PLHIV at the WPA Turen Foundation, Malang Regency. Methods: A descriptive quantitative study with a cross-sectional design was employed. Thirty PLHIV respondents were recruited through purposive sampling from a total population of 59 PLHIV at the WPA Turen Foundation. Data were collected using validated family support and quality of life questionnaires adapted from Kusuma (2011). Bivariate analysis was conducted using the Spearman rho test at a significance level of α = 0.05. Results: The majority of respondents received non-supportive family support (60%) and reported a good quality of life (53.3%). The Spearman rho test yielded p = 0.005 (p < 0.05) with a correlation coefficient of r = 0.355, indicating a statistically significant positive relationship of moderate strength between family support and quality of life among PLHIV. Conclusion: A significant relationship exists between family support and quality of life among PLHIV at the WPA Turen Foundation. The more supportive the family, the better the individual's quality of life. Family-based interventions, including HIV/AIDS education and family counseling, are recommended to sustainably improve the quality of life of PLHIV.